T‐cell profiles elicited by Toxoplasma gondii in acutely/chronically infected humans. (30th April 2018) - Silva‐Gutierrez, N.; Bahsas Zaky, R.; Bouchard, M.; Teran Angel, G.; Amoroso, A.; Peterson, D. L.; Salmen, S.
Summary: Toxoplasma gondii (T. gondii) is an obligate intracellular protozoan parasite that can infect almost all warm‐blooded species and induce a chronic infection in human hosts. The aim of this work was to investigate Th1, Th2, Th17 and Treg polarization, induced by four important T. gondii antigens (SAG1, ROP1, GRA8 and MAG1) in acutely and chronically infected patients. For this purpose, SAG1, ROP1, GRA8 and MAG1 were expressed as recombinant proteins, purified, and used to evaluate the proinflammatory and regulatory immune response profiles in seropositive and seronegative individuals. Our results show that SAG1 and ROP1 elicited a proinflammatory profile (INF‐γ, IL‐12 and IL‐17) in individuals in the acute phase, whereas MAG1 and GRA8 induced a regulatory pattern (Treg and TGF‐β) in chronically infected patients. These results reveal fundamental differences in T‐cell polarization induced by T. gondii antigens, which could have important implications in the immunopathogenesis of the disease and in future proposals of therapeutic strategies.